Patient experience of communication consistency amongst staff is related to nurse-physician teamwork in hospitals - Mia vonKnorring; Peter Griffiths; Jane Ball; Sara Runesdotter; Rikard Lindqvist (Wiley, 2020)
Abstract Aim To investigate whether nurse reported teamwork with physicians was associated with patient perceived consistency in staff‐to‐patient communication. Design A cross‐sectional survey design was used, drawing on data collected from two surveys in England. Methods Teamwork was assessed using data from the RN4CAST survey of 2,990 nurses in 31 Trusts in England. Data on patient experience derived from the National Health Services Adult Inpatient Questionnaire, including 12,506 patients in the same Trusts. A cross‐sectional design with multivariate logistic regression was used. Results Each 5% increase in the proportion of nurses who agree that there "is a lot of teamwork between nurses and physicians" was associated with 7% lower odds that patients reported inconsistency in communication amongst staff. The results suggest that patients seem to experience the consequences of less teamwork between nurses and physicians through their own perceptions of inconsistency in communication between staff. The findings emphasize good teamwork between doctors and nurses are not only important for the team, but also can have consequences for patients. It provides additional incentive to find mechanisms to breakdown disciplinary barriers and improve the cohesion of clinical teams for the benefit of their patients.